Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms231810647
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evaluation of Hexamethylene Amiloride Derivatives as Potential Luminal Inhibitors of SARS-CoV-2 E Protein

Abstract: The coronavirus E proteins are small membrane proteins found in the virus envelope of alpha and beta coronaviruses that have a high degree of overlap in their biochemical and functional properties despite minor sequence variations. The SARS-CoV-2 E is a 75-amino acid transmembrane protein capable of acting as an ion channel when assembled in a pentameric fashion. Various studies have found that hexamethylene amiloride (HMA) can inhibit the ion channel activity of the E protein in bilayers and also inhibit vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…E-protein is crucial for viral genome packaging and the synthesis of ion channels (IC), which are vital for virus-host contact and are frequently associated with pathogenicity 15 , 31 , 46 . We have observed one amino acid mutation of Proline (P) to Leucine (L) at the 71 st locus in the E-protein of SARS-CoV-2 (South Africa).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…E-protein is crucial for viral genome packaging and the synthesis of ion channels (IC), which are vital for virus-host contact and are frequently associated with pathogenicity 15 , 31 , 46 . We have observed one amino acid mutation of Proline (P) to Leucine (L) at the 71 st locus in the E-protein of SARS-CoV-2 (South Africa).…”
Section: Discussionmentioning
confidence: 99%
“…E-proteins are polypeptides with approximately 100 residues that are miniature components of virions but are extensively synthesized within infected cells 47,48 . They exhibit a small hydrophilic N-terminus, one or more putative terminal transmembrane (TM) domains, and a less hydrophobic C-terminal tail (15). Previously, it was demonstrated that SNPs within the TMD domain of the E-protein impaired IC function and resulted in reduced viral virulence 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, other ion channel inhibitors (pharmacophores), among the aromatic heterocyclic compounds that can strongly bind to proteins, were investigated, such as the spirene guanidine analogue, 2-[3-azaspiro (5,5) undecanol]-2-imidazoline (BL-1743) [ 117 ]. Other molecules, such as tauroursodeoxycholic acid as hexamethylene amiloride [ 118 ], gliclazide [ 119 ], memantine and other flavonoids such as epigallocatechin and quercetin were also effective [ 112 ].…”
Section: Viroporins As Targets For Viral Treatmentmentioning
confidence: 99%